2018
DOI: 10.3389/fnut.2018.00076
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices for Handling and Administration of Expressed Human Milk and Donor Human Milk for Hospitalized Preterm Infants

Abstract: The importance of human milk for the preterm infant is well established (1–3). However, the feeding of human milk to preterm infants is typically much more complicated than the mere act of breastfeeding (3, 4). The limited oral feeding skills of many preterm infants often results in human milk being administered via an enteral feeding tube (4). In addition, fortification is commonly required to promote optimal growth and development—particularly in the smallest of preterm infants (2, 4, 5). Consequently, a mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 24 publications
1
33
0
1
Order By: Relevance
“…In our study, improper hand washing was associated with EBM contamination. This is consistent with the conclusions of Steele, 23 who noted that hand washing with aseptic techniques is valuable in preservation of bacterial growth to acceptable levels.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, improper hand washing was associated with EBM contamination. This is consistent with the conclusions of Steele, 23 who noted that hand washing with aseptic techniques is valuable in preservation of bacterial growth to acceptable levels.…”
Section: Discussionsupporting
confidence: 92%
“…Actually, many studies have indicated that fresh milk should be cooled before adding to cold milk in the fridge and that stored milk should be rotated using first-in-first-out (FIFO) principles with the oldest milk being used first. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Некоторые ОРИТН предпочитают пастеризовать собственное молоко матери, чтобы снизить инфекционные риски, связанные с кормлением недоношенных младенцев с ОНМТ и ЭНМТ, до безопасного уровня [40]. В большинстве ОРИТН молоко матери не пастеризуется [30,41]: его либо сразу выдают недоношенному ребенку [30,40,41], либо хранят замороженным [30,40,41], а затем размораживают, прежде чем выдать для кормления. Процесс обработки (замораживания-размораживания) осуществляется обученным персоналом в специально отведенных помещениях [41][42][43].…”
Section: обеспечение микробиологической безопасности свежесцеженного unclassified
“…The American Academy of Pediatrics recommends exclusive breastfeeding for 6 months followed by continued breastfeeding as complementary foods are introduced for $1 year 13 because of the firmly established beneficial effects of breastfeeding. [14][15][16][17][18][19] We speculated that the ability of human milk to promote coagulation may contribute to these beneficial effects by, for example, triggering coagulation upon gastrointestinal vascular damage. If so, the coagulant activity of TF in human milk should be able to survive the digestive conditions encountered in an infant's gastrointestinal system.…”
Section: Introductionmentioning
confidence: 99%